Distribución espacial y estacional del ictioplancton en dos sistemas lagunares de la Reserva de la Biosfera de Sian Ka’an, Quintana Roo, México - Sanvicente-Añorve, Laura; Chiappa-Carrara, Xavier; Ocaña-Luna, Alberto (Revista de Biología Tropical, 1999)
Spatial and temporal variations in the composition and abundance of ichthyoplankton species in two lagoonal systems of ¡he Sian Ka’an Biosphere Reserve, are described. These systems display a great heterogcneity of physical parameters due to the concourse of marine, fresh, and underground waters. Surface simultaneous lowings with planklon nets of 200 and 500 μm mesh were oblained in four climatic periods, from October 1996 lo August 1997. Physical data were acquired with a salinity-conductivity meter. Fourty ichthyoplankton taxa identified include 25 genera and 21 species. Gobiidae, Hemirhamphidae, Atherinidae, Clupeidae, and Engraulidae families were well represented throughout the entire cycle. Our results show that salinity variations determine the presence of some species in the studied systems.